2009
DOI: 10.1080/09500830902802657
|View full text |Cite
|
Sign up to set email alerts
|

Validating the model of a (3 + 1)-dimensional incommensurately modulated structure as generator of a family of compounds for the Eu2(MoO4)3scheelite structure

Abstract: To cite this Article Martinez-Garcia, J., Arakcheeva, A., Pattison, P., Morozov, V. and Chapuis, G.(2009) 'Validating the model of a (3 + 1)-dimensional incommensurately modulated structure as generator of a family of compounds for the Eu 2 (MoO 4 ) 3 scheelite structure ',Philosophical Magazine Letters,89:4,[257][258][259][260][261][262][263][264][265][266] To link to this Article: DOI: 10.1080/09500830902802657 URL: http://dx.doi.org/10.1080/09500830902802657Full terms and conditions of use: http://www.infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…According to the scheme proposed for SRC, 14 the I2/b(ab0)00 (3 + 1)D superspace group has been applied here for all other incommensurately modulated structures and earlier for Eu 3+ 2/3 MoO 4 . 17 The phase with x ¼ 0.134 has been refined along with 6% of an additional phase with x ¼ 0.015. The crystallographic data are shown in Table 1.…”
Section: X-ray Diffraction Experimentsmentioning
confidence: 99%
“…According to the scheme proposed for SRC, 14 the I2/b(ab0)00 (3 + 1)D superspace group has been applied here for all other incommensurately modulated structures and earlier for Eu 3+ 2/3 MoO 4 . 17 The phase with x ¼ 0.134 has been refined along with 6% of an additional phase with x ¼ 0.015. The crystallographic data are shown in Table 1.…”
Section: X-ray Diffraction Experimentsmentioning
confidence: 99%
“…Self-activated phosphors are characterized by an almost complete absence of structural defects, and the precise determination of the crystal structure makes it possible to evaluate the relations between the Eu 3+ ion coordination in the lattice and spectroscopic characteristics of the compound. Simple europium stoichiometric compounds with tetrahedral MO 4 units, where M = Mo, W and S, were thoroughly studied and their applicability as highly efficient polyfunctional materials was shown [54][55][56][57][58][59][60][61][62][63][64][65][66][67]. At the same time, the properties of complex compounds of monovalent cations and rare-earth elements with tetrahedral anions are presented quite sporadically in the literature [37,[48][49][50][51]53,[68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive structural study of the R 2 (MoO 4 ) 3 molybdates was initially reported by Nassau et al Later, the structural data on different modifications of the R 2 (MoO 4 ) 3 molybdates were revised, and it was shown that the stability of different crystal forms depends on both the rare earth element and thermal treatment conditions. Generally, these compounds can be divided into two groups, having scheelite-type and non-scheelite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these compounds can be divided into two groups, having scheelite-type and non-scheelite structures. Among the scheelite-type R 2 □(MoO 4 ) 3 (where □ indicates a cation vacancy) structures, four variants are known with random or ordered distribution of the cations and vacancies: (1) tetragonal (space group (SG) I 4 1 / a ); (2) monoclinic (SG C 2/ c ) with the La 2 (MoO 4 ) 3 -type structure; (3) monoclinic (SG C 2/ c ) with the Eu 2 (WO 4 ) 3 -type structure (usually termed α-phases) (Figure a); and (4) monoclinic with the incommensurately modulated Pr 2 (MoO 4 ) 3 -type structure (superspace group (SSG) I 2/ b (αβ0)­00) . The ordering of cation vacancies in the scheelite-type R 2 □(MoO 4 ) 3 compounds depends on the R element.…”
Section: Introductionmentioning
confidence: 99%